Necrotizing Fasciitis: Diagnostic Challenges and Current Practices. (22nd January 2014) - Vijayakumar, Abhishek; Pullagura, Rajeev; Thimmappa, Durganna
Abstract : Necrotizing fasciitis or necrotizing soft-tissue infections (NSTIs) are infrequent but highly lethal infections. They can be defined as infections of any of the layers within the soft tissue compartment (dermis, subcutaneous tissue, superficial fascia, deep fascia, or muscle) that are associated with necrotizing changes. At onset, necrotizing fasciitis can be difficult to differentiate from cellulitis and other superficial infections of the skin. In fact, only 15% to 34% of patients with necrotizing fasciitis have an accurate admitting diagnosis. Early diagnosis and management with surgical debridement, antimicrobials, and supportive measures reduce mortality. Even with modern ICU care mortality ranges between 16 and 36%; this is related to delays in diagnosis and comorbidities. Various scoring systems have been developed which help in diagnosis and stratifying patients into risk groups. The present review deals with varied presentation, early diagnosis, and management of necrotizing fasciitis.